Formulation of Hand Sanitizer Gel from Passion Fruit (Passiflora Edulis Sims.) Leaf Extract and its Antibacterial Activity Against Staphylococcus Aureus and Escherichia Coli - Muhammad Maulana Yusuf; Fith Khaira Nursal; Etin Diah Permanasari (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Hand sanitizer is a widely used antiseptic preparation for reducing microbial contamination on the hands. This study aimed to develop and evaluate the physical characteristics and antibacterial activity of a hand sanitizer gel formulated with ethanol extract of passion fruit leaves (Passiflora edulis Sims.). The extract was obtained through maceration using 96% ethanol and subsequently formulated into three gel formulations (F1, F2, and F3) with varying extract concentrations. The gel base consisted of Carbopol 940 as a gelling agent, triethanolamine (TEA) as a pH adjuster and neutralizing agent, glycerin as a humectant, and methyl paraben as a preservative. Physical evaluations included organoleptic assessment, pH, spreadability, adhesion, and viscosity, conducted over 12 weeks of storage at 4°C and 40°C. Antibacterial activity was assessed using the disc diffusion method against Escherichia coli and Staphylococcus aureus. The results showed that all formulations produced a homogeneous, semisolid gel with good physical stability. The measured pH, spreadability, adhesion, and viscosity values of all formulations remained within the acceptable range for topical gel preparations. Antibacterial testing demonstrated that activity increased with higher concentrations of the extract. Among the formulations, F3 exhibited the strongest antibacterial effect, with inhibition zone diameters of 11.8 mm against Escherichia coli and 14.3 mm against Staphylococcus aureus. Overall, these findings indicate that passion fruit leaf ethanol extract can be successfully formulated into a stable and effective hand sanitizer gel with antibacterial properties.